Ecological Network Analysis of the Water-Energy-Food Metabolic System Based on the MRIO Model: A Case Study for China’s Yangtze River Delta Region - Yinwen Huang; Dechun Huang; Jinqiu Li (Complexity)
Water, energy, and food are essential resources for social and economic development, which are highly interwoven in the urban metabolic processes. The 2011 Bonn conference first introduced the concept of water-energy-food (WEF) nexus to describe the interconnection of three resources. In this study, taking the Yangtze River Delta region as a case study, we proposed a hybrid framework to quantify WEF consumption based on an environmentally extended multiregional input-output model. Then, various ecological network analyses were adopted to explore system properties and sectoral interaction. The results indicate that embodied WEF consumption in interregional trade is highly interconnected, in which Jiangsu accounts for the largest proportion of hybrid energy network, while Anhui dominates the hybrid water network and the food network. The recycling rate in the water network (14.5%–20.8%) is lower than that in the energy network (16.7%–23.5%) and the food network (17.2%–23.9%). Predation and exploitation relationships are dominated between sectors, and the whole trade network stays in a low positive environment. The nexus impact on water networks is smaller than that on the energy networks. This analysis may help identify leverage points and feasible pathways of crossregional resources’ trade and provide insights for integrated resources management of the Yangtze River Delta region.